DAMPAK GLOBALISASI TERHADAP PERKEMBANGAN KESADARAN PENGHORMATAN HAK ASASI MANUSIA DI INDONESIA - Rahayu Rahayu (Masalah-Masalah Hukum, 2010)
Globalization is a transformation process of social relations in the form of network of activities, interaction and trans-continental and inter-regional concessions and it is a worldwide phenomenon. Globalization also brings up threat for human security, that is a condition that requires the fulfillment of human basic needs in which human dignity must be respected and his participation in the life of community must be realized. This condition has an impact on the change of security concept from State centrism to human security At least seven factors must be fulfilled to realize human security, thats are: economic security, food security, health security, environmental security, personal security, community security and political security. The global awareness motivates the development of the concept, doctrine, norms and institution of Human Rights by making international consensus approved by International Community. This consensus is meant to determine the International standards and quality for the countries in implementing their duties to protect, promote, enforce and fulfill Human Rights. This consensus brings about some duties for the countries bound in it to implement the principles and rules in national domain (pacta sunt servanda). Globalization, indicated by the increasing intensity of inter-country relation and more problems regulated in International Law, results in bigger International Obligation of the countries in the world, among others is the obligation to maintain orderliness and peace in the world and to improve Human Rights